The Logical-Linguistic Model of Fact Extraction from English Texts - Khairova, N. F.; Petrasova, S. V.; Gautam, Ajit Pratap Singh (My University, 2016)
In this paper we suggest the logical-linguistic model that allows extracting required facts from English sentences. We consider the fact in the form of a triplet: Subject > Predicate > Object with the Predicate representing relations and the Object and Subject pointing out two entities. The logical-linguistic model is based on the use of the grammatical and semantic features of words in English sentences. Basic mathematical characteristic of our model is logical-algebraic equations of the finite predicates algebra. The model was successfully implemented in the system that extracts and identifies some facts from Web-content of a semi-structured and non-structured English text.
Keywords: logical-linguistic model; fact extraction; finite predicates algebra; triplet; grammatical features; syntactic features